KEDUDUKAN MASYARAKAT HUKUM ADAT DALAM PENGELOLAAN HUTAN ADAT PASCA PUTUSAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA NOMOR 35/PUU-X/2012 - SITI HADIJAH PULUNGAN (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Runtung2. Syafruddin Kalo3. Faisal Akbar Nasution The problem of tenure or the state’s right to control becomes the main source of conflict in adat forest management because of the uncertainty in the status of adat law community on their forest area and because of the uncertainty in the boundary of forest area. Article 18 B, paragraph 2 and Article 28 I, paragraph 3 of the 1945 Constitution recognize community’s adat law but they are still in general so that they need to be explained in detail. Law No. 41/1999 recognizes community’s adat law but does not recognize its management. The Constitutional Court’s Ruling No. 35/PUU-X/2012 emphasizes the position of community’s adat law and their forest management. Law No. 41/1999 regulates State’s Forest Management and Right Forest, but does not mention adat forest. Since the issuance of the Constitutional Court’s Ruling No. 35/PUU-X/2012 for more than four years ago, there has been no implementation of the Ruling because there is no legal umbrella with the same level of law which regulates recognition and protection for adat law community’s rights, so that it is necessary to take strategic measures in implementing the Ruling.Keywords: Community’s Adat Law, Adat Forest Management